Hydrogenation of nitrobenzene on Au/ZrO2 catalysts - Gómez, Samuel (2012)
The hydrogenation of nitrobenzene at 298K and pressure of 40 bar of H2 over zirconia supported Au catalysts has been studied. Three different procedures were used to prepare 1wt% of Au/ZrO2 catalysts: i) An impregnation method using HAuCl4 as gold precursor ii)Depositation precipitation of Au nanoparticles generated in the presence of urea and iii) Deposition of Gold nanoparticles generated in presence of cetryltrimethylammonium bromide (CTMABR) as surfactant. The catalysts were characterized by nitrogen adsorption-desorption isotherms at 77 K, XRD, TEM and XPS techniques. The reactions were carried out in a stainless steel batch reactor using ethanol as solvent. The catalysts exhibits a higher selectivity to aniline, with low accumulation of intermediate products. The kinetic study displayed orders 1 respect to hydrogen pressure and to the substrate concentration (nitrobenzene), and the activation energy was 67.2 KJ/mol